APPROACH TO CHRONIC PAIN IN PRIMARY HEALTH CARE (REMUNOM, 2025)
Objective: To understand the approaches used in the management of chronic pain in primary health care. Methods: This is an integrative review study on the approach to chronic pain in primary health care based on articles from the last 10 years. Results: The biopsychosocial model stands out as a guiding framework for more humanized and comprehensive care, requiring health professionals to provide qualified listening, individualized planning, and joint work with other team members. Conclusion: The analysis of the studies included in the review showed that musculoskeletal chronic pain is highly prevalent in primary health care and directly impacts patients’ functionality and well-being.